CONDITIONALITY AND INSTITUTIONAL TRANSFORMATION IN A NEOPATRIMONIAL CONTEXT - Movchan, Uliana (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The article examines the limited effectiveness of conditionality applied by international organizations in the implementation of institutional reforms in neopatrimonial states. The aim of the study is to identify why reforms initiated by international organizations result in formal, but not substantive, changes in the functioning of political institutions. The study analyzes the approaches of international organizations to reform implementation, in particular the normatively oriented mechanism of the European Union based on the transfer of the acquis and monitoring of formal compliance, the technocratic approach of the World Bank aimed at institutional design and the depoliticization of governance, as well as the conditional lending practices of the International Monetary Fund, associated with financial incentives and short-term performance criteria. Their structural limitations, arising from a focus on formal, measurable outcomes, are identified. The interaction between formal institutional change and informal practices in the context of neopatrimonialism is also examined, where patron-client networks and personalized governance shape actual political dynamics. Mechanisms of strategic compliance, adaptation, and selective implementation of reforms that allow elites to maintain control over resources are highlighted. Special attention is paid to the case of energy sector reforms in Ukraine, which demonstrates the coexistence of formal institutional arrangements with the reproduction of informal practices. It is argued that the limited effectiveness of conditionality is structural in nature and stems from its inability to incorporate informal institutions into the logic of reform. The article concludes that there is a need to rethink the approaches of international organizations to reform, taking into account the political nature of informal institutions.